Primary microstructure characterization of Co-20Ni-9Al-7W-3Re-2ti superalloy - Tomaszewska A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The characterization of the primary microstructure of the new Co-based superalloy of Co-20Ni-9Al-7W-3Re-2Ti type was shown in this article. The investigated alloy was manufactured by induction melting process from pure feedstock materials. The fundamental technological problem related to Co-Al-W-X multicomponent alloys casting process is a strong susceptibility to interdendritic segregation of alloying elements, especially tungsten and rhenium. The performed analysis revealed that the observed effect of alloying elements segregation was detectable and much stronger than for Co-9Al-9W and Co-20Ni-7Al-7W alloys, related to titanium, nickel, and aluminium migration to inter-dendritic spaces. Consequently, the tungsten concentration gradient between dendritic and interdendritic zones was higher than for Co-9Al-9W and Co- 20Ni-7Al-7W alloys. The same situation was in the case of rhenium and cobalt, but Co concentration in the interdendritic zone was only slightly lower.